Juvenile onset ankylosing spondylitis with ankylosing tarsitis: a rare combination - Siddiq, AB; Hasan, SA; Abdullah, AM; Azad, SA; Khan, EH; Khasru, MR (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):179-183 The abstract of this article is available on the PubMed website